Direct ionizing radiation and bystander effect in mouse mesenchymal stem cells. (2nd November 2022) - Nogueira-Pedro, Amanda; Segreto, Helena Regina Comodo; Held, Kathryn D.; Ferreira Junior, Antonio Francisco Gentil; Dias, Carolina Carvalho; Hastreiter, Araceli Aparecida; Makiyama, Edson Naoto; Paredes-Gamero, Edgar Julian; Borelli, Primavera; Fock, Ricardo Ambrósio
Abstract: Purpose: This study aimed to evaluate the radiation-induced direct and bystander (BYS) responses of mesenchymal stem cells (MSCs) and to characterize these cells radiobiologically. Methods and materials: MSCs were irradiated (IR) and parameters related to DNA damage and cellular signaling were verified in a dose range from 0.5 to 15 Gy; also a transwell insert co-culture system was used to study medium-mediated BYS effects. Results: The main effects on directly IR cells were seen at doses higher than 6 Gy: induction of cell death, cell cycle arrest, upregulation of p21, and alteration of redox status. Irrespective of a specific dose, induction of micronuclei formation, H2AX phosphorylation, and decreased Akt expression also occurred. Thus, mTOR expression, cell senescence, nitric oxide generation, and calcium levels, in general were not significantly modulated by radiation. Data from the linear-quadratic model showed a high alpha/beta ratio, which is consistent with a more exponential survival curve. BYS effects from the unirradiated MSCs placed into companion wells with the directly IR cells, were not observed. Conclusions: The results can be interpreted as a positive outcome, meaning that the radiation damage is restricted to the directed IR MSCs not leading to off-target cell responses.